Evaluation of the safety and efficacy of a Polyzene-F nanocoated coronary stent system: A systematic review and single-arm meta-analysis - Bian, Jifang; Yang, Rongyuan; Wang, Dawei; Yu, Huimin; Liu, Yuan; Liu, Qing (Frontiers in Cardiovascular Medicine, 2023)
Background A stent for patients with coronary heart disease (CHD) provides a requirement for a long-term antiplatelet therapy because of the high possibility of the development of stent thrombosis. It was against this background that both Cobra and Catania Polyzene-F (PzF) stents were designed to reduce the occurrence of stent thrombosis (ST). In this study, we review the safety and effectiveness of a PzF-nanocoated stent. Methods This systematic review with the title was registered in PROSPERO (No.398781). The inclusion criteria were including studies among patients with PzF-nanocoated coronary stents and reported target vessel failure (TVF) and ST as the outcomes, and the exclusion criteria were excluding reported patients who could not receive the adjunctive medical therapies or without the necessary endpoints. Reports about PzF-nanocoated stents were searched in PubMed, Embase, and Web of Science and other sources. Because of the existence of few reports and a lack of comparison groups, a single-arm meta-analysis was conducted in R software (v3.6.2), using a random-effects model with the generic inverse variance method. After a heterogeneity test, assessment of evidence quality was conducted by using GRADE software. A funnel plot Egger's test was performed to evaluate publication bias, and a sensitivity analysis was done to determine the robustness of the overall effects. Results Six studies of 1,768 subjects were included. The primary endpoint that pooled the TVF rate was 8.9% (95% CI 7.5%–10.2%), which comprised the pooled cardiac death (CD) rate (1.5%, 95% CI 0%–3%), myocardial infarction (MI) rate (2.7%, 95% CI 0.4%–5.1%), target vessel revascularization (TVR) (4.8%, 95% CI 2.4%–7.2%), or target lesion revascularization (TLR) (5.2%, 95% CI 4.2%–6.4%), while the secondary endpoint ST was 0.4% (95% CI 0.1%–0.9%). The funnel plots of TVF, CD, TVR, and TLR did not show any serious publication bias, and TVF, TVR, and TLR showed evidence of moderate quality in GRADE assessment. The sensitivity analysis showed that TVF, TLR, and ST exhibited good stability (I2 = 26.9%, 16.4%, and 35.5%, respectively), while the other endpoints showed moderate instability. Conclusion These data indicated that the PzF-nanocoated coronary stents of the Cobra and Catania systems demonstrated good safety and efficacy in clinical application. However, the sample size of patients included in the reports was relatively small, and this meta-analysis will be updated if more studies are published in the future. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42023398781